CD3CD4gp130 T cells are associated with worse disease activity in systemic lupus erythematosus patients - Mohd Shukri, Nur Diyana; Aziz, Farah Izati; Wan Ghazali, Wan Syamimee; Che Hussin, Che Maraina; Kah, Keng Wong (Frontiers Media, 2021)
The receptors for IL-35, IL-12Rβ2 and gp130, have been implicated in the inflammatory pathophysiology of autoimmune diseases. In this study, we set out to investigate the serum IL-35 levels and the surface levels of IL-12Rβ2 and gp130 in CD3+CD4+, CD3+CD4─ and CD3─CD4─ lymphocyte subpopulations in systemic lupus erythematosus (SLE) patients (n=50) versus healthy controls (n=50). The potential T cell subsets associated with gp130 transcript (i.e. IL6ST) expression in CD4+ T cells of SLE patients was also examined in publicly-available gene expression profiling (GEP) datasets. Here, we report that serum IL-35 levels were significantly higher in SLE patients than healthy controls (p=0.038) but it was not associated with SLEDAI-2K scores. The proportions of IL-12Rβ2+ and gp130+ cells in SLE patients did not differ significantly with those of healthy controls in all lymphocyte subpopulations investigated. Essentially, higher SLEDAI-2K scores were positively correlated with increased proportion of gp130+ cells, but not IL-12Rβ2+ cells, on CD3+CD4+ T cells (r=0.425, p=0.002, q=0.016). Gene Set Enrichment Analysis (GSEA) of a GEP dataset of CD4+ T cells isolated from SLE patients (n=8; GSE4588) showed that IL6ST expression was positively associated with genes upregulated in CD4+ T cells vs myeloid or B cells (q<0.001). In an independent GEP dataset of CD4+ T cells isolated from SLE patients (n=9; GSE1057), IL6ST expression was induced upon anti-CD3 stimulation, and that Treg, TCM and CCR7+ T cells gene sets were significantly enriched (q<0.05) by genes highly correlated with IL6ST expression (n=92 genes; r>0.75 with IL6ST expression) upon anti-CD3 stimulation in these SLE patients. In conclusion, gp130 signaling in CD3+CD4+ T cell subsets may contribute to increased disease activity in SLE patients, and it represents a promising therapeutic target for inhibition in the disease.